Integrating Character Education: Conducting A Needs Analysis for Crafting Poetry Teaching Materials for University Students - Halimah, Halimah; Nuryani, Rina (JEDLISH : Journal Of Education and English Language Teaching, 2023)
This research aims to conduct a needs analysis for the development of teaching materials for poetry studies containing character education. The method used is development research (research and development). Product development is carried out according to the steps of the research and development model (Gall, Gall, and Borg 2003). Two data in the research were obtained through questionnaires and interviews. The data that has been collected from the questionnaire is then analysed statistically to obtain the average value of all respondents, while the qualitative data is analysed descriptively qualitatively. The research results show that students need teaching materials that are relevant to the curriculum, learning outcomes, student needs, and can be applied in students' daily lives. In the aspect of teaching material content, students need concise, clear, interesting and easy to understand descriptions of teaching material so as to create a sense of comfort and foster self-confidence, material that can provide new knowledge and integration of character values ​​in teaching material, availability of study steps poetry and instructions on how to do assignments, and the availability of various poems to study.